Co-digestion of cassava starch wastewater with buffalo dung for bio-hydrogen production. (7th June 2019) - Wadjeam, Parichat; Reungsang, Alissara; Imai, Tsuyoshi; Plangklang, Pensri
Abstract: Batch and continuous modes for bio-hydrogen production by co-digesting cassava starch wastewater with buffalo dung were investigated. Response surface methodology with central composite design was used to optimize the bio-hydrogen production conditions. A hydrogen production potential of 1787 mL H2 /L was achieved under optimal conditions of 2.84 g/L of NaHCO3, an initial pH of 6.77 and a total chemical oxygen demand (tCOD)/total nitrogen ratio of 42.36. A continuous stirred tank reactor was operated under the optimum conditions from batch mode to investigate the effects of hydraulic retention time (HRT) of 72, 60 and 48 h on hydrogen production. The highest hydrogen content, hydrogen production rate and hydrogen yield of 33%, 839 mL H2 /L.d and 16.90 mL H2 /g-CODadded, respectively, were achieved at a HRT of 60 h. The predominant hydrogen producer under the optimal conditions in batch mode was Clostridium sp. while Clostridium sp., Megasphaera sp. and Chloroflexi sp. were observed in the continuous hydrogen production mode at an optimal HRT. Graphical abstract: Image 1 Highlights: Cassava starch wastewater was co-digested with buffalo dung to produce hydrogen. NaHCO3 2.84 g/L, initial pH 6.77, COD/TN ratio 42.36 were optimal conditions. Hydrogen production potential of 1787 mL H2 /L was achieved in batch mode. HRT 60 h in CSTR had the highest HY of 16.9 mL H2 /g-CODadded . Pre-dominant hydrogen producers were Clostridium sp.